Imipenem Resistance among Gram-Negative and Gram-Positive Bacteria in Hospitalized Patients - A Khorshidi; AR Sharif (Tehran University of Medical Sciences, 2010)
Background: Recent analyses of hospital outbreaks have documented the spread of resistance to imipenem, which is currently a major problem among gram positive and gram-negative bacteria. The aim of this study was to describe the rate of gram- positive and gram-negative isolates resistance to imipenem as an antibiotic. Methods: Recorded files of 242 hospitalized patients with at least one sample of positive culture specimens in one of the two general hospitals of Shahid Beheshti and Naghavi in Kashan, Iran in 2005 were randomly selected and reviewed. All strains were tested for antibiotic susceptibility by Disk Diffusion and were designated for imipenem. Results: Escherichia coli (21.9%), Kelebsiella (19.8%) and coagulase-negative Staphylococci (17.8%) were the most common isolated organisms. Imipenem had coverage against 96.2% of Escherichia coli, 58.4% of Kelebsiella, 79.1% of coagulase-negative Staphylococci, 81.8% of Pseudomonas aeruginosa, and 85.7% of Entrococci isolates. Proteus and Salmonella isolates susceptibility to imipenem was 100%. Conclusion: Susceptibility of Escherichia coli, Salmonella and Proteus to imipenem is satisfactory; however, the susceptibility of Pseudomonas aeruginosa to this antibiotic was dramatically lower in our region. Because of the major health problems caused by imipenem resistance, attempts have been made to organize a national surveillance program in our country.